The validation of Chinese version of workplace PERMA-profiler and the association between workplace well-being and fatigue - Chen-Cheng Yang; Hsiang-Tai Chen; Kuei-Hau Luo; Kazuhiro Watanabe; Hung-Yi Chuang; Chih-Wei Wu; Chia-Yen Dai; Chao-Hung Kuo; Norito Kawakami (BMC, 2024)
Abstract Background Well-being is an important issue in workplace. One of these assessment tools of well-being, Workplace PERMA Profiler, is based on Seligman's five dimensions well-being. Prolonged fatigue may last for a long time, leading a great impact on both employees and enterprises. However, rare studies about the association between well-being and fatigue had been investigated. Our aim is to establish the Chinese version Profiler, and to discovery the association between workplace well-being and fatigue. Methods The Chinese version was established according to International Society of Pharmacoeconomics and Outcomes Research (ISPOR) task force guidelines. In the study, researchers employed simple random sampling by approaching individuals undergoing health checkups or receiving workplace health services, inviting them to participate in a questionnaire-based interview. Prolonged Fatigue was evaluated by Checklist Individual Strength (CIS). The reliability was evaluated by Cronbach's alphas, Intra-class Correlation Coefficients (ICCs), and measurement errors. Moreover, confirmatory factor analysis and correlational analyses were assessed for the validity. Results The analyses included 312 Chinese workers. Cronbach's alphas of the Chinese version ranged from 0.69 to 0.93, while the ICC ranged from 0.70 to 0.92. The 5-factor model of confirmatory factor analysis revealed a nearly appropriate fit (χ2 (82) = 346.560, Comparative Fit Index [CFI] = 0.887, Tucker-Lewis Index [TLI] = 0.855, Root Mean Square Error of Approximation [RMSEA] = 0.114, Standardized Root Mean Square Residual [SRMR] = 0.060). Moreover, the CIS and its four dimensions were significantly and negatively associated with the Positive Emotion, while they are positively associated with Engagement dimension except CIS-Motivation dimension. Conclusion The Chinese version Workplace PERMA-Profiler indicate nice reliability and validity. Furthermore, all CIS dimensions were negatively influenced by Positive Emotion, while commonly positively associated with Engagement.